TELAAH HUKUM OMNIBUS LAW DAN PERLINDUNGAN TENAGA KERJA INDONESIA (Perspektif Undang-Undang No: 11 Tahun 2020 Tentang Cipta Kerja) - Mohammad Bangsu; Rachmat Ihya'; Nor Cholis (JURNAL LEGISIA, 2023)
Law Number 11 of 2020 concerning Job Creation, one of which regulates labor rights. Labor rights are the company's obligation to workers which must be protected by the State through law, therefore the state must be present to ensure that its citizens get their rights in working in order to meet the basic needs of citizens' lives so that the welfare of the Indonesian people can be achieved. This is in accordance with the 1945 Constitution, namely the state creates welfare and progress of the nation. The method in this study uses normative law, namely doctrinaire legal research methods or library research by analyzing the law as a primary source of law and literary literacy.  Theproblem caused by the enactment of Law Number 11 of 2020 concerning Job Creation is the reduction of labor rights, such as there are several articles that are deleted and added that are considered impartial to workers, for example in article 79 of the Job Creation Law, it is stated that overtime is carried out 4 hours in 1 day and 18 hours a week. The extended overtime time from the provisions of the Manpower Law 32/2003 states that overtime work time can only be done at most 3 (three) hours in 1 (one) day and 14 (fourteen) hours in 1 (one) week. In addition, the calculation of wages changes according to the company's ability and worker productivity, so it has the potential to be unsuitable for wages received by workers, to the threat of female workers because they do not get a salary when on menstrual and maternity leave.